Quantum dots : a survey of the properties of artificial atoms - Chakraborty, T. (Tapash), 1950-; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1999)
This book deals with the electronic and optical properties of two low-dimensional systems: quantum dots and quantum antidots and is divided into two parts. Part one is a self-contained monograph which describes in detail the theoretical and experimental background for exploration of electronic states of the quantum-confined systems. Starting from the single-electron picture of the system, the book describes various experimental methods that provide important information on these systems. Concentrating on many-electron systems, theoretical developments are described in detail and their experimental consequences are also discussed. The field has witnessed an almost explosive growth and some of the future directions of explorations are highlighted towards the end of the monograph. The subject matter is dealt with in such a way that it is both accessible to beginners and useful for expert researchers as a comprehensive review of most of the developments in the field. Furthermore the book contains 37 reprinted articles which have been selected to provide a first-hand picture of the overall developments in the field. The early papers have been arranged to portray the developments chronologically, and the more recent papers provide an overview of future direction in the research.
1. Introduction. 2. Quantum dots. 2.1. One-electron systems. 2.2. Dipole matrix elements. 2.3. Basic properties: experiments. 2.4. Transport spectroscopy. 2.5. Many-electron systems. 2.6. Electron-impurity systems. 2.7. Exciton spectrum. 2.8. Tilted field effects. 2.9. Spin blockade in quantum dots. 2.10. Quantum dot molecules. 2.11. Non-circular dots. 3. Related topics. 4. Summary and outlook. References. List of reprinted articles. Reprinted articles. Subject index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Quantum dots; Semiconductors; Quantum electronics; SCIENCE -- Physics -- Electromagnetism; SCIENCE -- Physics -- Electricity; Quantum dots; Quantum electronics; Semiconductors; Kwantummechanica; Electronic books